Validation of the Well-being Manifestations Measurement Scale (WBMMS) on a Sample of Russian Students - Tatiana G. Fomina; Irina N. Bondarenko (Lomonosov Moscow State University, 2024)
Background. The article presents a comparative analysis of diagnostic tools used to assess various aspects of psychological well-being. It also outlines trends in the development of modern survey methods for its assessment. The objective of this study is to substantiate the advantages of the methods that allow diagnosing both the general level of psychological well-being and its separate components (eudemonic and hedonic), taking into account contextual and age-related aspects. The results of the validation of the questionnaire "Well-being Manifestations Measurement Scale (WBMMS)" on a sample of Russian students are presented. Study Participants. The sample consisted of 435 Russian university students, the age ranging from 16 to 28 years (Mage = 19.72, SD = 1.67). Of these, 56.41% were female and 44.52% were male. Methods. The following methods were employed: the scale of general level of subjective well-being (Life Satisfaction Scale) by E. Diener, the scale of optimism (Test of Dispositional Optimism, TDO-P), and the Depression Scale of the Center for Epidemiological Studies, CES-D. Results. The results of the confirmatory factor analysis (CFA) supported our initial hypothesis that the well-being construct could be adequately represented by a single common factor, formed by two lower-order factors. These factors, eudemonistic and hedonistic, respectively, were significantly correlated with each other, and with the subjective well-being of participants. The instrument demonstrated good convergent validity with these variables, as indicated by the positive correlation with subjective well-being and the negative correlation with optimism. The questionnaire scales exhibited satisfactory reliability values. A comparison of female and male samples on the scales of the SPPB questionnaire indicated the necessity to consider gender in the development of the questionnaire norms. Conclusions. The scale of manifestations of psychological well-being meets contemporary psychometric standards and allows for the assessment of psychological well-being in accordance with the latest theoretical approaches. The results obtained contribute to both the theoretical understanding of the construct of well-being and its measurement.